Effect of glucagon-like peptide-1 receptor agonists in patients with psoriasis. (April 2014) - Al-Badri, Marwa R.; Azar, Sami T.
Glucagon-like peptide-1 (GLP-1) agonists are a class of drugs used for the treatment of type 2 diabetes mellitus. GLP-1 is released in response to meal intake; these classes of drugs enhance glucose-dependent insulin secretion and exhibit other antihyperglycemic effects following their release into the circulation from the gut. Psoriasis is a chronic skin condition affecting approximately 2% of the Western population. It is considered to be an autoimmune disease that involves the Th1 pathway and is associated with metabolic syndrome and its components, such as obesity, diabetes, and hypertension. We have reviewed reports in the literature that indicate a beneficial anti-inflammatory effect of GLP-1 in patients with diabetes or who have insulin resistance and psoriasis.